Peran Basyarnas dalam Penyelesaian Sengketa Ekonomi Syariah (Studi Pandangan Pelaku Ekonomi Syariah di Jakarta) - Irfan, M. Nurul Irfan; Faizin, Afwan; Muslim, Bukhori (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
National Shariah Arbitration Board (Basyarnas) is one of the manifestations of the first established Islamic Arbitration in Indonesia. Basyarnas stands autonomously and independently as one of the legal instruments that resolve disputes of the parties, whether coming from within the environment of Islamic banks, Takaful Insurance, or any other party who needs it. In connection with the Basyarnas function, this article discusses the following three main issues: Firstly, the view of sharia economic actors on Basyarnas. Shariah economic actors generally consider the importance of Basyarnas’s position in settling disputes in Sharia economics. In the last five years (2010-2015) the number of disputes cases in Basyarnas (23 cases) is slightly higher than cases handled by the Religious Courts (20 cases). Secondly, the reason for sharia economic actors chooses the arbitration route because the process is faster, the cost is light and the verdict is final and binding and the secrets of the parties are maintained. Thirdly, the factors that influence the choice are also determined by the level of confidence of the sharia economic actors to the judges’ ability within the Religious Courts to resolve the dispute.